The role of gene polymorphisms in individually changing of the lipid profile among patients with coronary artery disease under the influence of the statin therapy - I. M. Fushtey; E. V. Sid; V. V. Litvinenko (Сучасні медичні технології)
Ischemic heart disease is one of the urgent problems in modern cardiology, which is associated with a wide spread of disability and mortality mainly among young and employable aged people. The therapeutic drugs effect is individual and depends on the genetic characteristics of the patient. The aim of the study. Analysis of modern literature sources related to the role of gene polymorphisms in individual lipid profile changing among patients with coronary artery disease under the influence of the statin therapy.